Sequences of presidential-term-Limit reforms: Latin America and sub-Saharan Africa. Issue 1 (2nd January 2022) - Heyl, Charlotte; Llanos, Mariana
ABSTRACT: In this article we take a longitudinal view on presidential-term-limit reforms in Latin America and sub-Saharan Africa since the third wave of democratization. Many countries in the two regions (re-)introduced term limits at this time as a democratic safeguard against personal rule and power abuses. Since then, term limits have been contested by a plethora of reform attempts. Such reforms are commonly seen as a risk to democracy since stable institutions are considered essential for democratic consolidation, while term-limit eliminations are associated with processes of autocratization. From the literature on democratic consolidation, institutionalization and presidential-term-limit reforms we distil theoretical expectations on term-limit-reform paths across time and examine how they relate to the evolution of the political regime. To empirically investigate reform paths across regions we apply the research method of sequence analysis. We find that the stability of term-limit rules is more prevalent than expected, but that this stability sometimes masks institutional ineffectiveness under authoritarian regimes. Rule instability induced by frequent reforms can be part of a piecemeal path towards autocratization, but it can also reflect an open-ended tug of war between authoritarian tendencies and democratic resistance.